Sociocultural factors influencing physiotherapy management in culturally and linguistically diverse people with persistent pain: a scoping review. Issue Volume 107:Issue (2020) (June 2020) - Yoshikawa, Koji; Brady, Bernadette; Perry, Meredith A.; Devan, Hemakumar
Abstract: Background: People with persistent pain from culturally and linguistically diverse (CALD) communities experience significant health inequities. Objective: To synthesise the sociocultural factors influencing pain management between CALD patients with persistent pain and physiotherapists treating CALD patients. Data sources: Major electronic databases MEDLINE, AMED, Scopus, Web of Science, PsycINFO and Google Scholar were searched until July 2018. Study selection: Studies were included if they explored clinical interactions between physiotherapists and patients with persistent pain from diverse ethnocultural backgrounds. Study appraisal: The methodological quality of qualitative and quantitative studies were assessed using the Critical Appraisal Skills Programme (CASP) Checklist and Mixed Methods Appraisal Tool (MMAT) respectively. Synthesis method: A thematic synthesis approach was used to extract the common themes. Results: Sixteen articles from 16 studies were included. Eleven studies were qualitative and five studies were quantitative. Ten explored patients' perspectives, four explored physiotherapists' perspectives, and two explored both. Key factors included: (a) language competence; (b) active vs passive coping strategies; (c) gendered influences; (d) cultural-spiritual beliefs, illness perceptions and expression of pain; (e) treatment satisfaction and; (f) barriers to access. Conclusion: Discordant perspectives on causation, pain management approaches, and patient autonomy in management are evident between CALD patients and physiotherapists. Such discordance potentially create stress in the therapeutic alliance and undermines the efficacy of pain management interventions. To mitigate such barriers, it is crucial to foster cultural competence in physiotherapy and equip physiotherapists with opportunities to maximise their sociocultural awareness, knowledge and skill practising physiotherapy in cultural plural societies.